Achalasia: current therapeutic options. (June 2017) - Arora, Zubin; Thota, Prashanthi N.; Sanaka, Madhusudhan R.
Achalasia is a chronic incurable esophageal motility disorder characterized by impaired lower esophageal sphincter (LES) relaxation and loss of esophageal peristalsis. Although rare, it is currently the most common primary esophageal motility disorder, with an annual incidence of around 1.6 per 100, 000 persons and prevalence of around 10.8/100, 000 persons. Symptoms of achalasia include dysphagia to both solids and liquids, regurgitation, aspiration, chest pain and weight loss. As the underlying etiology of achalasia remains unclear, there is currently no curative treatment for achalasia. Management of achalasia mainly involves improving the esophageal outflow in order to provide symptomatic relief to patients. The most effective treatment options for achalasia include pneumatic dilation, Heller myotomy and peroral endoscopic myotomy (POEM), with the latter increasingly emerging as the treatment of choice for many patients. This review focusses on evidence for current and emerging treatment options for achalasia with a particular emphasis on POEM.